Prevalence of low back pain and its associated factors among traditional cloth weavers in Gulele sub-city, Addis Ababa, Ethiopia - Amare Terfe; Temima Jemal; Tolossa Waqkene (Frontiers Media S.A., 2023)
The prevalence of work-related musculoskeletal disorders particularly low back pain is significantly high among common informal or small-scale enterprises within developing countries like weaving. However, there is little information on risk factors for low back pain in the informal sector such as the weaving sector in the areas of Addis Ababa as well as in Ethiopia. Therefore this study was aimed to assess the magnitude of low back pain and its associated factors among traditional cloth weavers in the Gulele sub-city, Addis Ababa, Ethiopia. A cross-sectional study with internal comparison was conducted from June 1, 2022, and August 30, 2022. A total of 660 traditional cloth weavers were included in the study by using a systematic random sampling method to select participants in each of cooperatives as well as individual households in 5 woredas in Gulele sub-city. The data was analyzed and managed using SPSS version 20. A multivariate logistic regression analysis was used to control potential confounding factors and to determine the association. Among 660 (100%) respondents, 330 (50%) of them experienced low back pain after starting weaving. Out of the respondents with low back pain through their job career, 291 (44.1%) of them experienced low back pain during the last 12 months. Working greater than 8 h per day (AOR = 4.60, 95%CI: 2.35, 8.87), working with frequent bending (AOR = 3.32, 95%CI: 1.49, 7.40), job stress (AOR = 1.68, 95%CI: 1.18, 2.40) were among factors significantly associated with the occurrence of low back pain. This study has shown a high prevalence of low back pain among traditional cloth weavers which indicates the need for immediate public health action. However, very small improvements in the working condition, weaving tools design, working methods can potentially lead to large benefits.